1992
DOI: 10.1152/ajpregu.1992.263.1.r9
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic NaCl inhibits gastric motility and food intake in rats with lesions in the rostral AV3V region

Abstract: Several diverse treatments that stimulate pituitary secretion of oxytocin (OT) in rats produce a parallel inhibition of gastric motility and food intake. The present experiments demonstrate that injection of hypertonic saline (HS) is another such treatment. Systemic administration of large doses of OT had no effect on gastric motility. Lesions within the region anteroventral to the third ventricle (AV3V region) severely impaired the drinking response to HS without affecting its inhibition of either gastric mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The OVLT plays a major role in hyperosmolality-stimulated thirst (19,27,28,44,48) and pituitary release of vasopressin (30,44,48) and oxytocin (17,35). To date, however, involvement of OVLT in mediating hyperosmolality-induced increases of SNA has not been directly assessed.…”
Section: Discussionmentioning
confidence: 99%
“…The OVLT plays a major role in hyperosmolality-stimulated thirst (19,27,28,44,48) and pituitary release of vasopressin (30,44,48) and oxytocin (17,35). To date, however, involvement of OVLT in mediating hyperosmolality-induced increases of SNA has not been directly assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Before the present study, evidence to support a role for central OT in dehydration anorexia has come primarily from short-term experiments in rats in which osmotic dehydration is induced by systemic administration of hypertonic solutions, and OT signaling is manipulated by central administration of OT receptor agonists and antagonists. Such experiments have demonstrated that OT-containing projections from the PVN to the DVC provide a tonic hypothalamic inhibition of vagally mediated gastric motility and emptying (8,29), that this inhibitory influence is amplified during osmotic dehydration (9), and that OT receptor blockade attenuates both dehydration-induced inhibition of gastric emptying and dehydration anorexia (23).…”
Section: Effect Of Water Deprivation To Increase Hindbrain Fos Immunomentioning
confidence: 99%
“…Circulating AVP promotes renal retention of water, whereas OT promotes renal excretion of sodium in rats (40). Dehydration also inhibits gastric emptying and food intake (8,30,32,34,42), which together help limit absorption of additional osmoles into the circulation. Finally, dehydration stimulates compensatory drinking of water, when it is available; the subsequent absorption of water into the circulation helps to restore both intracellular and extracellular fluid compartments (31, 34).…”
mentioning
confidence: 99%
“…Since hypophagia accompanies states of osmotic dehydration in adult rats, it is significant that this behavioral effect is blunted by central antagonism of OT receptors (Olson, Drutarosky, Stricker, & Verbalis, 1991a). In adult rats, the OT-containing projection from the PVN to the DVC provides a tonic inhibitory influence over vagally mediated gastric motility that is further amplified by plasma hyperosmolality (Flanagan, Blackburn, Verbalis, & Stricker, 1992b;Rogers & Hermann, 1992). Microinjection of OT into the DVC increases the activity of neurons there that receive synaptic input from gastric viscerosensory afferents (McCann & Rogers, 1990), consistent with a role for OT signaling within the DVC to underlie an indirect control of food intake.…”
Section: A Functional Model For the Postnatal Emergence Of Hypothalammentioning
confidence: 99%
“…Centrally mediated responses to plasma hyperosmolality in adult rats include compensatory drinking, neurohypophyseal secretion of OT and vasopressin (Stricker & Verbalis, 1986), inhibition of vagally mediated gastric motility and emptying (Flanagan et al, 1989;Flanagan et al, 1992b), and inhibition of food intake (Flanagan, Dohanics, Verbalis, & Stricker, 1992a). The first two responses also occur in neonatal rats (Almli, 1973;Bruno, 1981;Sinding, Robinson, & Seif, 1980), whereas the latter hypophagic response, termed ''dehydration anorexia,'' does not emerge until after the first 2 weeks of postnatal development (Bruno, 1981;Bruno & Hall, 1982;Callahan & Rinaman, 1998).…”
Section: A Functional Model For the Postnatal Emergence Of Hypothalammentioning
confidence: 99%